Muscle Contributions to Knee Loads in Healthy Young Women - Longpré, Heather Sarah (My University, 2015)
Lower extremity muscles are primary contributors to knee loading during static and dynamic activities. The underlying philosophy of this thesis contends that a more robust understanding of the relationships between muscle function and the loading environment in the healthy knee is needed for clinicians to prescribe effective lower extremity muscle training programs. The primary objectives were to (i) identify changes in knee mechanics and muscle function during gait, static squats and lunges after lower extremity neuromuscular fatigue, (ii) explore relationships between knee loading, and peak knee extensor and flexor strength and power, and (iii) identify isometric standing muscle training postures which elicit minimal medial knee loads. In the studies addressing objective (i), isotonic lower extremity fatigue reduced the peak knee extension moment during gait, decreased vastus lateralis activation, and decreased mean knee moments during static lunging. These findings indicated that fatigue altered muscle recruitment strategies and may have concurrently altered the knee loading environment during these submaximal tasks. However, these biomechanical alterations are not consistent with those in knee osteoarthritis or ligament injury. In the studies addressing objective (ii), peak knee extension torque and power were important in describing healthy knee loading during the early and late stance phases of gait, respectively. Finally in the studies addressing objective (iii), isometric muscle training postures were identified which targeted quadriceps and hamstrings muscle activation without overloading the medial compartment of the knee. Muscle activation levels required to increase lower limb torque production capacity can be achieved by performing squats and lunges and these postures elicit lower knee moments than those experienced during gait. This work expands the understanding of healthy knee function and the relationships between muscle function and mechanical knee loading. These insights will contribute toward the future creation of muscle training programs and guidelines for knee OA or ACL injury.